TOWARDS THE ISSUE ON DEMAND GENERATION IN THE SERVICE MARKET - A. N. Krylov; G. P. Kuzina; A. I. Mozgovoy (Вестник университета)
The features of supply and demand in the service market, the main trends in the market of household services, its dynamics for the period from 2010 to the present in the Russian Federation have been considered. The level of influence of marketing tools on the customer’s perception (collaboration, full information about the service, advertising campaign, employee motivation, presentation of new products, etc.) has been studied, the results of the study have been given, the main measures for creating demand for a company providing consumer services, event budget have been defined. An economic assessment of the effectiveness of the proposed measures in the form of an expected increase in revenue and payback periods has been given. Using the proposed set of measures will allow you to actively influence the process of forming the company’s demand in the market of household services.